Cultural and emotional intelligence correlates with healthy lifestyles - Keisuke Kokubun; Kiyotaka Nemoto; Yoshinori Yamakawa (Acta Psychologica)
A healthy lifestyle is essential to prevent illness and live a happy life. Previous research has shown that social intelligence, such as emotional intelligence (EQ) and cultural intelligence (CQ), is related to a healthy lifestyle. However, there are fewer studies that clarify the relationship between CQ and lifestyle compared to EQ and lifestyle, and the relationship between the facets that make up these intelligences and lifestyle is also unclear. Therefore, in this study, we aimed to clarify the relationship between the eight facets of these intelligences and the seven lifestyles by multiple regression analysis and relative importance analysis. As a result, consistent with the Self-Regulated Learning (SRL) strategy theory, which is based on motivation and metacognition, it was shown that the two intelligences, Use of emotion EQ and Metacognitive CQ, were most broadly correlated with the five lifestyles, and Self-emotional appraisal EQ was also correlated with the two lifestyles. These results suggest that in today's globalized society, in addition to the intelligence required to understand and utilize one's own emotions, there is a need for intelligence to understand different cultures and to verify and correct the accuracy of knowledge about them.